2016
DOI: 10.1504/ijil.2016.073306
|View full text |Cite
|
Sign up to set email alerts
|

Role of transitory communities of practice in business school collaborative knowledge-sharing projects: from the partner's perspective

Abstract: This paper explores the essential roles that academics, graduates/post-graduates and small enterprise owner-managers play when working together on knowledge-sharing projects The study uses six projects to explore the life cycle of these transitory Communities of Practice (CoP) and how they can provide an effective means for sharing knowledge and expertise. This investigation is significant as such sharing of knowledge and expertise is the basis of the increasingly informal knowledge management structures such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…They opened up to teachers due to more trust as a result of empathy shown during the planning on a lesson and an experiment. This collaboration is the reflection of trust and is the foundation of learning and development [2].…”
Section: Discussionmentioning
confidence: 99%
“…They opened up to teachers due to more trust as a result of empathy shown during the planning on a lesson and an experiment. This collaboration is the reflection of trust and is the foundation of learning and development [2].…”
Section: Discussionmentioning
confidence: 99%
“…Trust and integrity as social values, perceived by employees on their leaders, can enable opportunities for knowledge creation and application, and at the same time contribute to building trust inside an organization (Park and Lee, 2014). Another important consideration is the expectation that members of an organization have, regarding that the process of KS generates decision-making actions (Brown and Frame, 2016). If the flow of information does not trigger decisions, it can be perceived as worthless and unnecessary, so it was usual to have this result from the survey which is matching the literature found.…”
Section: Discussionmentioning
confidence: 99%
“…Collaboration in the OC means having more flexibility and closely connecting employees working together. Brown and Frame (2016) identified collaboration as one of the strongest mechanisms for lowering barriers to effective interaction impacting organizational KS. In addition, Smith and Laycock (2005) and Alshamsi et al (2017) explained that collaboration captured the spirit of KS and represented a strong factor supporting KS within the organization.…”
Section: Knowledge Sharing Key Factors With Theoretical Lensmentioning
confidence: 99%
“…Talat et al [61] evidenced the mediating role of knowledge sharing between the variables of organizational culture oriented to learning and spirituality in the workplace. For their part, Brown and Frame [62] identified collaboration as the mechanism through which organizational culture facilitates knowledge sharing. In the same direction, Memon et al [63] reported a relationship between an organizational culture that encourages its workers and the sharing of tacit knowledge.…”
Section: Knowledge Sharing and Culturementioning
confidence: 99%